Biochemical genetics of some Indian fishes - Menezes, Maria R; Quasim, S Z (Indian Journal of Fisheries, 2011)
In this paper an attempt has been made toevaluate the present status ofthe biochemicalgenetic research in fishes. At the same time,we have given the importance of this field ofstudy and also indicated what we regard as themost fruitful areas for future research.